PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH - Defitri, Siska Yulia (Jurnal Ekobistek, 2017)
This study aims to determine whether the participation of budget preparation and budget goal clarity and simultaneous partial effect on the performance of local government officials in Solok City Government. The hypothesis in this study are the effect of partially or simultaneously budgetary participation and budget goal clarity on the performance of local government officials in Solok City Government.This type of research is causative. The population in this study are all the people involved in the budget planning SKPD Se-Solok totaling 41 SKPD. The sample selection using purposive sampling. The data used in this study are primary data. Data collection techniques by distributing questionnaires. The data analysis technique used is multiple regression with the help of Statistical Package For Social Science (SPSS).Research shows that participation budgeting and clarity of budget targets positive significant effect on the performance of local government officials. F shows that the budgetary participation and budget goal clarity together or simultaneously significant effect on the performance of local government officials. Results of statistical processing regression analysis showed a significant value on the table F 0.05 is calculated F value 3.145 7.023 0.002 significant. Thus 7.023 F count> F table 3.145 with significant value of 0.002 <0.05. Keywords: Participation Budgeting, Clarity Budget Targets and Performance of     Local Government Officials.